1994
DOI: 10.2527/1994.7292395x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of growth by intravenous injection of copper in weanling pigs

Abstract: This study was conducted to examine whether Cu could exert its growth-promoting effect when injected, rather than being fed, and thus bypass the gastrointestinal tract. In two 18-d experiments, pigs were injected every 2 d with a Cu histidinate or histidine solution. Amounts of Cu injected were calculated to simulate varying absorption rates in pigs fed 250 ppm of dietary Cu. In Exp. 1, 44 pigs were randomly assigned to four groups of 11 pigs each. Pigs were injected with four levels of Cu histidinate (0, 5, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
49
0
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 23 publications
6
49
0
10
Order By: Relevance
“…This can be assumed considering the chemical similarity of silver with other metals such as zinc and copper and the characteristics of their antimicrobial response. The capability of zinc and copper to minimise the negative effect of weaning on the of height of intestinal villi, thus ensuring its absorbing potential (Li et al, 2001) and the enhancement of the metabolic pancreatic activity (Zhou et al, 1994) could also be potentially expected with the use of silver. Besides, studies related with the role of silver nanoparticles on wound treatment show its role on metalloproteinases regulation, reducing inflammation and favouring cellular apoptosis and cicatrisation (Wright et al, 2002;Warriner & Burrell, 2005).…”
Section: Other Effects Of Silvermentioning
confidence: 99%
See 1 more Smart Citation
“…This can be assumed considering the chemical similarity of silver with other metals such as zinc and copper and the characteristics of their antimicrobial response. The capability of zinc and copper to minimise the negative effect of weaning on the of height of intestinal villi, thus ensuring its absorbing potential (Li et al, 2001) and the enhancement of the metabolic pancreatic activity (Zhou et al, 1994) could also be potentially expected with the use of silver. Besides, studies related with the role of silver nanoparticles on wound treatment show its role on metalloproteinases regulation, reducing inflammation and favouring cellular apoptosis and cicatrisation (Wright et al, 2002;Warriner & Burrell, 2005).…”
Section: Other Effects Of Silvermentioning
confidence: 99%
“…The addition of high doses of zinc (from 2500 to 3500 ppm, as zinc oxide) or copper (from 150 to 250 ppm, as copper sulphate) modulates the microbial status of the digestive tract and reduce the incidence of post-weaning diarrhoea (Jensen-Waern et al, 1998;Broom et al, 2006), generally promoting increases in productive performances (Hill et al, 2000;Case & Carlson, 2002). However, it remains unclear to what extent the response is associated with its role over the digestive microbial ecosystem (Hogberg et al, 2005) or directly over the piglet metabolism (Zhou et al, 1994), by affecting the secretion and activity of pancreatic and intestinal digestive enzymes or the maintenance of the morphology of the intestinal mucosa (Li et al, 2001;Hedemann et al, 2006). Considerable efforts have been made to look for alternatives to antibiotics growth promoters in animal feeding during the last three decades.…”
mentioning
confidence: 99%
“…Cu is mostly used as copper sulfate but Cromwell et al (1998) showed similar efficacy in the case of tri-basic copper chloride. The growth-stimulating properties of dietary copper have been attributed to its antimicrobial action however, it was shown that also intravenous injection of copper to weanling piglets stimulate their growth (Zhou et al 2014). It seems that the growth-promoting properties of high dietary concentrations of copper are in addition to its antimicrobial action (Jacela et al 2010).…”
mentioning
confidence: 99%
“…Nos componentes químicos do ganho de peso, a ingestão de Cu apresenta relação com a síntese protéica e lipídica em leitões (Luo & Dove, 1996). Na síntese protéica, foi relatado que o Cu estimula a secreção de hormônios de crescimento em leitões alimentados com dietas suplementadas com este mineral (Zhou et al, 1994). No metabolismo lipídico, o Cu aumenta a atividade de enzimas específicas que participam da biossíntese de ácidos graxos acil, alterando a deposição de lipídios (Ho & Elliot, 1974).…”
Section: Resultsunclassified